Phytobuffering of Lower Chlorinated Benzenes Through Willows at the PPI Superfund Site - P. B. Jones Jr.; R. R. Kommalapati; W. D. Constant (Journal of Hazardous Substance Research, 2001)
A series of phytobuffering bench-scale experiments using an extraction bed followed by a plant “bioreactor” was performed using streambed sediment from a nearby Superfund site. Experiments consisted of investigating the fate and transport of a mixture of lower chlorinated benzenes (monochlorobenzene, (MCB), 1,2 and 1,3- dichlorobenzene (DCB), and 1,2,4-trichlorobenzene (TCB)) at 10 – 20 ppm sediment loading. These compounds are representative of the degradation products of HCB (hexachlorobenzene) in the Baton Rouge Bayou and Devil’s Swamp area at the Petro Processors Inc. Superfund site. Fast, slow, and cyclic flow rates were used as representative conditions found during rain events in the area. Willow cuttings obtained from the site were developed into small plants to measure uptake in the dynamic system. The rates of plant capture of contaminants from contaminated sediment were experimentally estimated under various flow conditions and a mathematical model for the plant uptake rate of the plant “reactor” system was developed. Estimation of the buffering effect expected in these bayou-plant systems was determined by scale up of the kinetic data using the model results. Results indicated that for both steady and transient systems, the willow trees provided a significant buffering of the contaminant flux. Rate coefficients were obtained using an unsteady state analytical model and the experimental data. Cyclic flow resulted in the highest rate coefficients followed closely by slow flow, and the fast flow resulted in the lowest of the rate coefficients. Finally, based upon the uptake rates determined, projections were made by scaling up the developed model to 20 years (current site age) and over 100 acres (contaminated area of the swamp). The lower chlorinated benzenes buffered by the willows ranged from 34 tons for s
Keywords: phytoremediation; chlorinated benzenes; uptake rates; willow trees; attenuation